Analisis Deiksis Sosial dalam Bahasa Jepang: Kajian Sosiopragmatik - Fadhillah Hakim, Ruri; Komara Mulya; Shaniya Kinanti Prabawani (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2024)
This study aims to determine the types of social deixis, social factors, and social dimensions that cause the use of social deixis in the Japanese language. The background for this research is the awareness of the importance of referents or references in conversation based on social roles and societal differences to realize the right choice of words to maintain harmony and respect between the speech participants. The theories used in this study are the SPEAKING theory by Dell Hymes (1974) to analyze the context, the theory of Levinson (1983) as a reference regarding the types of social deixis, and the theory of Holmes (2001) as a reference to analyze social factors and social dimensions. Based on the analysis of 29 data, it is known that there are 9 data that contain more than one type of social deixis in one data. This happens due to several factors, such as context, speech participants, and the situation in the conversation being analyzed. Also, it can be concluded that the components of the social dimension become supporting and strengthening components of social factors that cause the usage of social deixis in speech.